Relações públicas e jogos educacionais: proposta de recurso didático para estimular o desenvolvimento de habilidades profissionais - Silva, Alexandra Gabrielly Rocha da (Brasil, 2020)
The present project has as objective to create a didactic resource that allowed the expansion and stimulation of knowledge on topics related to the profession of Public Relations, in a playful way, with a purpose of entry as it teaches. For this, it uses the questionnaires applications that use the knowledge about the topic covered, besides the bibliographical research about the public relations profession, crisis management and games. As a result, we achieved successfully the objective. The construction of the educational crisis management game that will be integrated into the Public Relations course for students. This way, it concludes that this work, combined with the final product, is a great value to improve the forms of teaching, expanding as possibilities of learning, critical thinking and debate in the classroom. In addition to offering the possibility of inspiration for new ways of improvement assist in the teaching of students.